ДНЕВНИК В. И. ИВАНОВОЙ: АВТОР И ТЕКСТ1 - Arustamova, Anna A. (Philological Studies, 2019)
The article examines the diary written by the resident of Novosiolovo village (Perm region) V. Ivanova. The diary is considered as a sample of naiive literature. The research is focused on such aspects as the diary structure of the modern village resident, ways of expressing author’s identity, the correlation of biographical and cultural aspects. The article explores combination of visual and textual elements as core elements of diary`s narrative.